2009
DOI: 10.5194/angeo-27-2019-2009
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of substorm injection region evolution: 27 August 2001

Abstract: Abstract. We present riometer and in situ observations of a substorm electron injection on 27 August 2001. The event is seen at more than 20 separate locations (including ground stations and 6 satellites: Cluster, Polar, Chandra, and 3 Los Alamos National Laboratory (LANL) spacecraft). The injection is observed to be dispersionless at 12 of these locations. Combining these observations with information from the GOES-8 geosynchronous satellite we argue that the injection initiated near geosynchronous orbit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“… Liu et al [2009b] observed magnetic field dipolarization signatures at ∼−11 R E to occur ∼90 s after tail reconnection signatures at ∼−20 R E . Spanswick et al [2009] studied a substorm on 27 August 2001 in detail, concluding that the magnetic field pulse took ∼8 min to propagate from −18 to −6.6 R E . Spanswick et al [2009] also reported that EEPs were observed on the ground near L = 6.6 and expanded both poleward and equatorward, consistent with the earlier riometer‐based survey of Berkey et al [1974].…”
Section: Introductionmentioning
confidence: 99%
“… Liu et al [2009b] observed magnetic field dipolarization signatures at ∼−11 R E to occur ∼90 s after tail reconnection signatures at ∼−20 R E . Spanswick et al [2009] studied a substorm on 27 August 2001 in detail, concluding that the magnetic field pulse took ∼8 min to propagate from −18 to −6.6 R E . Spanswick et al [2009] also reported that EEPs were observed on the ground near L = 6.6 and expanded both poleward and equatorward, consistent with the earlier riometer‐based survey of Berkey et al [1974].…”
Section: Introductionmentioning
confidence: 99%
“…For a number of events, they found that a sharp rise in plasma sheet electron flux for energies >30 keV (dispersionless injection) was often accompanied (under certain conditions) by a sharp rise in riometer absorption due to sudden enhancement of ionization in the lower ionosphere. If multiple riometers pick up this ionospheric signature of high energy particle precipitation, then tracking the movement of these signatures can give insight into the spatial and temporal evolution of the substorm injection region [Berkey et al, 1974;Liang et al, 2007;Liu et al, 2007;Spanswick et al, 2009]. In this study, we extend this ground-based method of identifying substorm precipitation signatures to GPS TEC, assuming that enhanced electron density due to high-energy particle precipitation will produce detectable TEC enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…Substorm injections are often dispersionless [McIlwain, 1974;Mauk and Meng, 1987] and are contained within a localized injection region characterized by a well-defined injection boundary at its edges [Reeves et al, 1991]. It has been shown that dipolarization and injection signatures are localized at substorm onset, and expand azimuthally [Thomsen et al, 2001] and radially [Spanswick et al, 2009] during the substorm's expansion phase. Azimuthal and radial expansion of the dipolarization fronts have been studied in detail using geosynchronous magnetic field data [Liou et al, 2002;Watson and Jayachandran, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This event has been already studied (Baker et al 2002;Li et al 2003;Eriksson et al 2004;Blake et al 2005;Spanswick et al 2009;Mishin et al 2012). We complement and expand on the previous results, thoroughly analyzing the role of the induction mechanism.…”
Section: Introductionmentioning
confidence: 99%